Upaya Kantor Urusan Agama Kecamatan Karanganyar dalam Menangani Kehamilan di Luar Pernikahan pada Tahun 2022–2024 - Gazza Adjie Saputra; S Syamsuddin (AL HUKMU: Journal of Islamic Law and Economics, 2026)
Marriage is a fundamental human need and an act of worship prescribed in Islam. The true purpose of marriage is to unite two individuals in a lawful bond in accordance with religious teachings and legal regulations. However, in contemporary society, juvenile delinquency has become increasingly common and concerning. One such issue is sexual misconduct, including cases where women become pregnant before marriage. This situation brings about negative impacts and causes public concern. This study aims to explore how the Office of Religious Affairs (KUA) in Karanganyar District handled cases of premarital pregnancy from 2022 to 2024. The research used a descriptive qualitative method, with data collected through interviews and literature review. The field data were then processed and analyzed to yield the findings. The results show that the Office of Religious Affairs in Karanganyar District plays a significant role not only in the administrative aspects of marriage but also as a moral and spiritual agent in addressing cases of premarital pregnancy. Through an approach that prioritizes ethics, privacy, and religious guidance, the KUA strives to ensure that couples entering marriage under pregnancy conditions can still build a responsible household. Although it is not yet equipped with professional psychological support systems, these efforts have contributed to reducing social unrest in the community.